2020
DOI: 10.3390/ijms21186855
|View full text |Cite
|
Sign up to set email alerts
|

P2Y Purinergic Receptors, Endothelial Dysfunction, and Cardiovascular Diseases

Abstract: Purinergic G-protein-coupled receptors are ancient and the most abundant group of G-protein-coupled receptors (GPCRs). The wide distribution of purinergic receptors in the cardiovascular system, together with the expression of multiple receptor subtypes in endothelial cells (ECs) and other vascular cells demonstrates the physiological importance of the purinergic signaling system in the regulation of the cardiovascular system. This review discusses the contribution of purinergic P2Y receptors to endothelial dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 148 publications
(211 reference statements)
1
25
0
Order By: Relevance
“…P2 receptors are composed of P2XRs, the ligand-gated cation channels, and the P2YR subtypes are stimulated by different endogenous nucleotides [ 442 ]. The different receptors are coupled to either Gq to activate PKC, Gs to activate cAMP, and Gi to inhibit cAMP [ 479 , 480 , 481 ]. Purinergic receptors P 2 Y 1 R, P 2 Y 2 R or P 2 Y 4 R, and P 2 Y 11 R promote adipogenic differentiation of stem cells derived from bone marrow or adipose tissue [ 447 ].…”
Section: Nucleotide-nucleoside Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…P2 receptors are composed of P2XRs, the ligand-gated cation channels, and the P2YR subtypes are stimulated by different endogenous nucleotides [ 442 ]. The different receptors are coupled to either Gq to activate PKC, Gs to activate cAMP, and Gi to inhibit cAMP [ 479 , 480 , 481 ]. Purinergic receptors P 2 Y 1 R, P 2 Y 2 R or P 2 Y 4 R, and P 2 Y 11 R promote adipogenic differentiation of stem cells derived from bone marrow or adipose tissue [ 447 ].…”
Section: Nucleotide-nucleoside Metabolitesmentioning
confidence: 99%
“…These results suggest that age-dependent increases in P2Y 6 R expression determine Ang II’s pathological vascular effects and cardiovascular risk. P 2 Y 6 R-deficient mice exhibit a decrease in Ang II-induced pathological arterial remodeling in response to hypertension than wild-type mice [ 503 ] P 2 Y 1 R and P 2 Y 13 R are expressed in pulmonary artery vasa vasorum endothelial cells and functionally involved in intracellular and mitochondrial Ca 2+ regulation associated with pathologic angiogenic expansion of the vasa vasorum network [ 479 , 505 ].…”
Section: Nucleotide-nucleoside Metabolitesmentioning
confidence: 99%
“…[65][66][67] However, related to the current discourse is the role of purinergic sensing in PH, which has seen a relative explosion in interest within the past several years. 68 Genomewide RNA studies have previously demonstrated alteration in the purinergic G-protein coupled receptor P2Y-family in patients with PAH and secondary PH, compared to healthy controls. 69 Mechanistically, blocking P2Y 1 and P2Y 12 receptors blocks adenosine diphosphate (ADP)-induced pulmonary vasoconstriction in pigs.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…There is experimental evidence supporting an important role of P2Y receptors in vasa vasorum neovascularization and pathologic vascular remodeling in PH [ 178 ]. Furthermore, in plexiform lesions from PAH patients, expression of CD39/ENTPD1, the ectonucleotidase responsible for the conversion of the nucleotides ATP and ADP to AMP, was decreased, suggesting that increased extracellular ATP level in the pulmonary vascular endothelium and within the angiomatoid proliferative lesions might contribute to excessive endothelial proliferation [ 44 ].…”
Section: Physiological Function and Dysfunction Of P2y2mentioning
confidence: 99%